Seroprevalence study of IgG anti CagA& IgA anti H.Pylori and their relationship to blood groups in Erbil city - Mousa Khaleel, Khoshawi; Rast Shawais, Kani; Ghulam Hussain, Saeed (Zanco Journal of Medical Sciences (ZJMS), 2026)
Background and objective: Helicobacter pylori is a worldwide bacterial pathogen that associated with increasing risk of gastritis peptic ulcer and gastric adenocarcinoma. Especially strains harbor cytotoxin associated gene A (CagA) which classified by WHO in the category of class 1 carcinogen. The study designed to assess seroprevalence of anti-Cag A IgG & anti-H.pylori IgA antibodies among asymptomatic GIT free manifestations among adult & children in Erbil /Kurdistan region. Linkage between seropositive H.pylori infection & ABO blood group, age, gender & smoking, were also verified. Methods: A total to 369 blood samples were collected from adult & child participant free of Gastrointestinal diseases. The sera were screened for anti- CagA IgG & anti -H pylori IgA antibody using ELISA assay. Further, the samples were subjected to ABO blood grouping using hemagglutination test. The result was statistically analyzed using chi-square test. Results: Seroprevalence of IgG anti-cagA positivity was 41.5% among adult which was significantly (P <0.001) higher than the frequency among children (22.1%). For IgG anti-H pylori, the prevalence was significantly (P <0.001) higher among adults than children (44.9% vs 14.4% respectively). The seroprevalence of mixedpositive IgG & IgA anti- H pylori antibodies was 28.7% among adults and 13.5% among children (P = 0.002). The rate of IgG & IgA seropositivity was higher among adult & children with Blood-group (O) although no significant association was detected. Conclusion: The findings of the present study suggest that anti-CagA IgG & Ig A seropositivity may correlate with infection by CagA-positive H. pylori strains, based on serological data alone. Therefore, this marker can be considered a useful non-invasive screening tool when molecular characterization of the CagA gene is unavailable, though direct genotyping the gold standard. Blood group type O was predominant among participant seropositive for anti- CagA IgG antibodies. The alarming finding in this study was the very high titers of anti-CagA IgG (>150) among the screened participant, which might be a risk factor for increased risk of gastric cancer.